Early warning indicator of economic vulnerability - Wong, Shirly Siew-Ling; Puah, Chin-Hong; Shazali, Abu Mansor; Liew, Venus Khim-Sen (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The initiative to capture the information content behind the rise and fall of the business cycle has popularized the study of leading indicators. Many of the foreign experiences shared by economically advanced countries reveal that the leading indicator approach works well as a short-term forecasting tool. Thus, exploring an indicator-based forecasting tool for business cycle analysis and economic risk monitoring would provide insight into the Malaysian economy as well as that of other emerging countries. By extending the ideology of indicator construction from the US National Bureau of Economic Research (NBER), the present study demonstrated the strong potential of the leading indicator approach to be a good gauge of the business cycle movement in addition to being a practical and functional early warning indicator for economic vulnerability prediction.